Mātauranga and science - Mercier, Ocean (New Zealand Science Review, 2018)
<span data-sheets-value="{"1":2,"2":"Mātauranga – Māori knowledge and Māori ways of knowing – developed in Aotearoa along with the cultural and epistemological identities of iwi Māori, thus is rooted in these islands and holds a well of human understanding of Aotearoa ecosystems. Mātauranga encompasses traditional and contemporary knowledge and is becoming increasingly sought after and integrated into mainstream education, research, and environmental policy in Aotearoa New Zealand. With ‘Vision Mātauranga’ a critical point of engagement for researchers, what does the scientist working in this space need to know about mātauranga? I have highlighted what I see to be key aspects of the discussion on how scientists work with those who hold and access mātauranga, and with mātauranga itself. The scholarly literature on mātauranga is extensive, so I focus on that which is relevant to science education and science research. Throughout I describe and explore the potential of research in which mātauranga and science connect and relate."}" data-sheets-userformat="{"2":769,"3":{"1":0},"11":4,"12":0}">Mātauranga – Māori knowledge and Māori ways of knowing – developed in Aotearoa along with the cultural and epistemological identities of iwi Māori, thus is rooted in these islands and holds a well of human understanding of Aotearoa ecosystems. Mātauranga encompasses traditional and contemporary knowledge and is becoming increasingly sought after and integrated into mainstream education, research, and environmental policy in Aotearoa New Zealand. With ‘Vision Mātauranga’ a critical point of engagement for researchers, what does the scientist working in this space need to know about mātauranga? I have highlighted what I see to be key aspects of the discussion on how scientists work with those who hold and access mātauranga, and with mātauranga itself. The scholarly literature on mātauranga is extensive, so I focus on that which is relevant to science education and science research. Throughout I describe and explore the potential of research in which mātauranga and science connect and relate.